Addressing Sexual Violence in Islamic Boarding Schools: A Study on Santri Perceptions and Institutional Responses - Eka Yuliana Rahman; Amri Dhimas Maulana (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: This study aims to explore santri perceptions of sexual violence in Islamic boarding schools in Banyuwangi Regency and assess the institution's response to the issue. It then observed how santri in boarding schools understand, identify, and respond to the issue of sexual violence, including their understanding of the signs of sexual violence and their attitudes towards reporting such cases. Methodology: This research uses a qualitative case study design, which allows researchers to explore phenomena in a real-life context. The research locations were several Islamic boarding schools located in Banyuwangi Regency that were selected based on certain criteria, such as having a history of sexual violence case reports or being willing to participate in this study. The participants of this research are santri (both victims and non-victims), boarding school caregivers, teachers, administrative staff, psychologists, and Banyuwangi police, as well as the surrounding community. For data collection techniques using participatory observation, in-depth interviews, forum group discussions, and documentation. Data analysis techniques used interview and FGD transcription, thematic analysis, and data triangulation. Main Findings: The results showed that santri perceptions of sexual violence are influenced by cultural factors, religion, and social norms in pesantren. These findings provide a deeper understanding of the dynamics of sexual violence in pesantren and can be the basis for formulating more effective policies and interventions in addressing this issue. This research also shows that social studies learning has great potential to contribute to efforts to prevent sexual violence in pesantren. Through civic education, social and moral values, and gender awareness, social studies can provide a foundation for santri to understand human rights, respect others, and play an active role in creating a safe and violence-free environment. Novelty/Originality of this study: The novelty of this study lies in its specific focus, comprehensive methodological approach, and practical implications that can help address the issue of sexual violence in Islamic boarding schools in a more effective way that is sensitive to the cultural, religious, social studies context.